Effect of systemic ozone therapy as a biomodulator of tissue regeneration and inflammatory response in rats - PIRES,Juliana Rico (2021)
Abstract Introduction Among the therapeutic effects of ozone therapy, improvement in cell metabolism and peripheral tissue oxygenation have been highlighted. Objective to evaluate the systemic effect of bio-oxidative therapy with ozone gas on wound healing. Material and method Tissue lesions with a circumference of 1.0 cm were induced in the skin on the back of 24 male Wistar rats. The animals were randomly divided into two groups: 1) Group C (control; n=12): with simulation of the application of ozone gas via the rectum and, 2) Group O3 (test; n=12): with application of ozone gas by means of rectal insufflation at a concentration of 50 µg/mL. The animals were euthanized at seven and 15 days, and samples were removed, fixed in formalin, and submitted to macroscopic, histological, and histometric analyses. Result The animals in the O3 group presented mixed inflammation at seven days, which translated into an absence of inflammation at 15 days. The C group exhibited acute inflammation on the 7th day, translating to chronic inflammation, which significantly increased from the 7th to the 15th day. The findings showed that the O3 group presented greater wound contraction (P<0.05) and a greater degree of neovascularization on the 7th day (P<0.05) when compared to group C. On the 15th day, both groups (O3 and C) showed complete re-epithelialization, however, the O3 group demonstrated complete muscle regeneration. Conclusion The systemic ozone therapy had a biomodulatory effect, reducing the characteristics of acute inflammation and increasing tissue repair and regeneration in rat skin.